Efficacy of a Novel Triple-Agent Germicidal Protocol for Residual Cavity Management Following Hepatic Echinococcectomy - Butaboev , Jasurbek; Shaykhova , Guli; Qosimov , Adham (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
Epidemiological metrics indicate a persistently high regional prevalence of cystic echinococcosis, demanding targeted evaluations of intraoperative parasitic eradication. The current investigation analyzes the multidimensional dynamics of residual cavity management following conservative hepatic echinococcectomy, utilizing a novel triple-agent protocol. The study population comprised 132 adult patients diagnosed with hepatic hydatid cysts, monitored over 36 months via a prospective, randomized-controlled design. Empirical clinical data demonstrate a robust inverse correlation between the application of the integrated germicidal solution (3 percent hydrogen peroxide, 20 percent hypertonic saline, and 0.02 percent chlorhexidine) and postoperative complication rates. Analytical outputs confirm that this targeted profiling optimizes intraoperative cavity sterilization, yielding a complete protoscoleces eradication rate of 100 percent within 5 minutes, compared to 87.8 percent in the standard hypertonic saline cohort. The dynamics of the obtained results mandate a shift from generalized monotherapy toward targeted chemical interventions. Patients subjected to the novel protocol exhibited a significantly reduced hospital stay (7.1 +/- 1.2 days versus 11.4 +/- 2.5 days) and zero parasitic recurrence. These findings bridge persistent literature gaps by validating a comprehensive chemical interaction model, establishing a rigorous foundation for future hepatobiliary surgical strategies.